First-principles DFT insights into the structural, elastic, and optoelectronic properties of α and β-ZnP2: implications for photovoltaic applications. (15th April 2019) - Živković, Aleksandar; Farkaš, Barbara; Uahengo, Veikko; de Leeuw, Nora H; Dzade, Nelson Y
Abstract: Binary II–V semiconductors are highly optically active materials, possess high intrinsic mechanical and chemical durability, and have electronic properties ideal for optoelectronic applications. Among them, zinc diphosphide (ZnP2 ) is a promising earth-abundant absorber material for solar energy conversion. We have investigated the structural, mechanical, and optoelectronic properties of both the tetragonal ( α ) and monoclinic ( β ) phases of ZnP2 using standard, Hubbard-corrected and screened hybrid density functional theory methods. Through the analysis of bond character, band gap nature, and absorption spectra, we show that there exist two polymorphs of the β phase (denoted as β 1 and β 2 ) with distinct differences in the photovoltaic potential. While β 1 exhibits the characteristics of metallic compounds, β 2 is a semiconductor with predicted thin-film photovoltaic absorbing efficiency of almost 10%. The α phase is anticipated to be an indirect gap material with a calculated efficiency limited to only 1%. We have also analysed and gained insights into the electron localization function, projected density of states and projected crystal orbital Hamilton populations for the analogue bonds between the α and β -ZnP2 . In light of these calculations, a number of previous discrepancies have been solved and a solid ground for future employment of zinc diphosphides in photovoltaics has been established.